Neural control of redox response and microbiota-triggered inflammation in Drosophila gut - Fuse, Naoyuki; Hashiba, Haruka; Ishibashi, Kentaro; Suzuki, Takuro; Nguyen, Quang-Dat; Fujii, Kiho; Ikeda-Ohtsubo, Wakako; Kitazawa, Haruki; Tanimoto, Hiromu; Kurata, Shoichiro (Frontiers in Immunology, 2023)
Background The neural system plays a critical role in controlling gut immunity, and the gut microbiota contributes to this process. However, the roles and mechanisms of gut-brain-microbiota interactions remain unclear. To address this issue, we employed Drosophila as a model organism. We have previously shown that NP3253 neurons, which are connected to the brain and gut, are essential for resistance to oral bacterial infections. Here, we aimed to investigate the role of NP3253 neurons in the regulation of gut immunity. Methods We performed RNA-seq analysis of the adult Drosophila gut after genetically inactivating the NP3253 neurons. Flies were reared under oral bacterial infection and normal feeding conditions. In addition, we prepared samples under germ-free conditions to evaluate the role of the microbiota in gut gene expression. We knocked down the genes regulated by NP3253 neurons and examined their susceptibility to oral bacterial infections. Results We found that immune-related gene expression was upregulated in NP3253 neuron-inactivated flies compared to the control. However, this upregulation was abolished in axenic flies, suggesting that the immune response was abnormally activated by the microbiota in NP3253 neuron-inactivated flies. In addition, redox-related gene expression was downregulated in NP3253 neuron-inactivated flies, and this downregulation was also observed in axenic flies. Certain redox-related genes were required for resistance to oral bacterial infections, suggesting that NP3253 neurons regulate the redox responses for gut immunity in a microbiota-independent manner. Conclusion These results show that NP3253 neurons regulate the appropriate gene expression patterns in the gut and contribute to maintain homeostasis during oral infections.